Relationships Social Environment and Self-Efficacy of Learning Results of Bugis Bridal Processes - Sabet, Meli; Atmanto, Dwi; Siregar, Jenny Sista; Wastira, Jarudin (Sukma: Jurnal Pendidikan, 2021)
The purpose of this study was to determine the relationship between social environment and self-efficacy on learning outcomes of Bugis bridal make-up. Using a quantitative approach with a correlation test. Purposive sampling technique is carried out by taking the subject not based on strata, random or regional but based on the existence of a specific goal, namely by involving 34 students who are following the subject of Bugis bridal make-up. Based on the results of the Pearson correlation test, it was shown that the relationship between social environment variables and learning outcomes of Bugis bridal make-up was obtained as â´-Value <Sig. 0.05 means it can be concluded that there is a relationship. The results of the correlation test for variable X2, namely Ï-value 0.247> 0.05, means that there is no significant relationship, while for the correlation test between social-environmental variables on self-efficacy it is obtained Ï-Value 402> Sig. 0.05, it can be concluded that the social environment variable has no significant relationship to the self-efficacy variable. that the social environment variables and self-efficacy together on learning outcomes of Bugis bridal make-up have no significant relationship because of Ï-Value 0.675> Sig. 0.05. This means that the social environment and self-efficacy cannot shape students to improve learning outcomes of Bugis bridal make-up.